Bullous pemphigoid as a paraneoplastic manifestation of metastatic adenocarcinoma of the lung - Adhimani, Sanjay L; Baikunje, Nandakishore; Hosmane, Giridhar Belur; Nair, Nandu (Indian Journal of Case Reports, 2024)
A 73-year-old male smoker presented with complaints of fever and multiple clear fluid-filled lesions for 3 months. He was initially being treated for primary bullous pemphigoid but lesions recurred. On a chest X-ray, he was found to have a right hilar mass, and contrast-enhanced computed tomography of the chest revealed a right lung mass lesion with cervical, hilar, and mediastinal lymphadenopathy. A bronchoscopy was done, and bronchoalveolar lavage cytology was suggestive of lung adenocarcinoma. An excision biopsy of the left supraclavicular lymph node showed features consistent with adenocarcinoma lung. Hence, he was diagnosed with metastatic adenocarcinoma of the lung with bullous pemphigoid as a paraneoplastic manifestation. He was subsequently treated with chemotherapy, and his skin lesions resolved.